Fiber sponge scaffold with improved mechanical properties and multi-site capture of copper ions and preparation method
By grafting phosphorus-containing crown macromolecules containing multiple pyrrole groups on the fiber sponge scaffold, a fiber sponge scaffold that can capture copper ions in multiple locations was prepared, which solved the problems of insufficient mechanical properties and unstable metal ion release. High mechanical performance and stable release functions suitable for bone repair are achieved.
Patent Information
- Application Number
- CN202211438670.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-11-17
AI Technical Summary
The existing fiber sponge scaffolds have poor mechanical properties and cannot be used for bone repair. At the same time, when used for bone repair, the release rate of loaded metal ions is uncontrollable, resulting in the problem of excessive or insufficient metal ions.
By grafting the short nanofiber sponge with the phosphorus-containing crown macromolecules containing multiple pyrrole groups, a fiber sponge scaffold that can capture copper ions in multiple locations is prepared, which improves its mechanical properties and achieves a long time The function of stably releasing copper ions.
It significantly improves the mechanical properties of the fiber sponge scaffold, making it suitable for bone repair, and captures and stabilizes copper ions through multi-site capture and stabilize release, promoting vascularization and bone regeneration, solving the problem of instability in metal ion release.
Smart Images

Figure CN116350852B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bioremediation materials, and in particular relates to a fiber sponge scaffold capable of improving mechanical properties and capturing copper ions at multiple sites, and a preparation method and application thereof. Background Art
[0002] Metal ions are important trace elements in the human body and play an important role in the normal life process of the human body, including maintaining life functions, regulating metabolism, promoting tissue repair, etc. Metal ions maintain a dynamic balance in the human body. Once the types and concentrations of metal ions in the body are out of balance, it will affect normal life activities and lead to the occurrence of related diseases.
[0003] In the field of tissue engineering repair, metal ions have been widely used and play an important role in the process of tissue regeneration. Among them, zinc ions are used to promote the proliferation of tendon cells, iron ions have been shown to have important abilities to promote cell migration and cell homing; copper ions can promote the osteogenic and angiogenic differentiation of mesenchymal stem cells. Therefore, combining metal ions with biorepair materials for tissue regeneration has become a hot topic in research.
[0004] Researchers have developed biomaterials for loading metal ions, including hydrogels, nanofiber membranes, and bioactive glass. However, most of these metal ion carriers use methods that directly mix or graft metal ions with various biomaterials, which have the following disadvantages: (1) There is a lack of specific chelation between the material and the metal ions; (2) The release rate of metal ions after loading is uncontrollable, and the unstable release of metal ions in the body can easily lead to excessive accumulation of metal ions in the short term, causing damage to tissues and the body; (3) There is a problem of insufficient metal ion concentration in the long term, resulting in poor tissue repair effects.
[0005] Nanofibers have a high aspect ratio, specific surface area and porosity, and have a similar structure to the natural extracellular matrix (ECM), which can provide more adhesion sites to support cell adhesion and growth. Therefore, nanofibers are very important one-dimensional nanomaterials. On this basis, people have developed nanofiber membranes by controlling the orientation and stacking of fibers. However, two-dimensional electrospun fiber membranes are mostly made of tightly packed nanofiber layers, which usually have small pore sizes, low porosity, and lack of three-dimensional structures in a practical sense, which limits the three-dimensional growth of cells and the regeneration of specific tissues.
[0006] In recent decades, researchers have made many new attempts to reshape two-dimensional nanofiber membranes into three-dimensional scaffolds, and have achieved great research results. At present, a variety of bionic ECM nanofiber three-dimensional scaffolds have been developed, among which electrospun nanofiber sponges, as a porous sponge three-dimensional scaffold with highly bionic ECM properties, have received widespread attention in the field of tissue engineering. A large number of studies have shown that nanofiber sponges have good application prospects as tissue engineering repair scaffolds, which can promote vascularization and efficient cell adhesion and growth.
[0007] Studies have found that the chemical composition, structure and mechanical properties of the biomaterial itself affect the level of vascularization, especially the mechanical properties of the biomaterial have a great influence on vascularization. For example, one study found that HUVEC cultured on soft collagen gel (6kPa) is more likely to undergo morphological changes than on hard collagen gel (10kPa), and is conducive to the formation of more vascular network structures (Sieminski et al, The relative magnitudes of endothelial force generation and matrix stiffness modulate capillary morphogenesis in vitro [J], Experimental Cell Research, 2004). Another study also showed that endothelial cells migrate faster and generate more lymphatic vessels on soft matrices (0.2kPa) (Frye et al, Matrix stiffness controls lymphatic vessel formation through regulation of a GATA2-dependent transcriptional program [J], Nature Communications, 2018). Different series of results all show that matrix hardness can regulate capillary morphogenesis in vitro, stem cells are more likely to differentiate into endothelial cells on soft substrates, and endothelial cells are more likely to form functional blood vessels.
[0008] Therefore, in order to improve the vascularization ability of nanofiber sponges, most people pursue the bulkiness of the fibers and the formation of a large porosity. However, this also leads to low mechanical properties of the nanofiber sponges, which can only be used for implantation in soft tissues such as skin and heart and repair of wounds, but cannot be used for repairing bone defects.
[0009] Since the scaffolds used for bone defect repair have high requirements for mechanical properties, nanofiber sponge materials with good vascularization cannot be used for bone repair due to their poor mechanical properties.
[0010] In order to solve the problem of poor mechanical properties of nanofiber sponge scaffolds, most of the existing methods are to increase the fiber density of the fiber sponge or increase the fiber dosage to improve the mechanical strength of the material. However, due to the uncontrollable fiber distribution, other properties of the material are affected, and on the other hand, the preparation cost and operation complexity are increased.
[0011] Therefore, how to improve the mechanical properties of nanofiber sponge scaffolds and ensure the various properties of implant materials has become a major problem in applying them in the field of bone repair.
[0012] On the other hand, since the combination of metal ions and scaffolds plays a good role in promoting bone repair, how to achieve active capture and stable release of metal ions on the basis of improving the mechanical properties of nanofiber sponge scaffolds has become another research difficulty.
[0013] Therefore, how to find a method to improve the mechanical properties of nanofiber sponge scaffolds in order to use them for bone repair, and how to stably maintain the basic properties of the material so that the nanofiber sponge scaffolds can meet the requirements of long-term implantation of bone repair materials, has become one of the technical problems to be solved urgently. On the other hand, on the basis of being able to improve the mechanical properties of nanofiber sponge scaffolds, how to achieve active recruitment and multi-site capture of metal ions to promote vascularization and bone regeneration, and to achieve long-term stable release of captured metal ions, has become another technical problem to be solved urgently in this field. Summary of the invention
[0014] The purpose of the present invention is to solve the above technical problems, thereby providing a fiber sponge scaffold capable of improving mechanical properties and capturing copper ions at multiple sites, and a preparation method and application thereof. The technical purpose of the present invention is to: on the one hand, solve the problem that the existing fiber sponge scaffold has poor mechanical properties and cannot be used for bone repair, and provide a fiber sponge scaffold capable of improving mechanical properties; on the other hand, on the basis of improving the mechanical properties of the fiber sponge scaffold, provide a fiber sponge scaffold capable of actively capturing metal ions at multiple sites, and capable of stably releasing the captured metal ions for a long time for angiogenesis and promoting bone regeneration, so as to solve the problem that the existing metal ion-loaded scaffold is not ideal when used for bone repair and cannot release metal ions for a long time.
[0015] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0016] One of the purposes of the present invention is to provide a method for preparing a fiber sponge scaffold capable of improving mechanical properties and capturing copper ions at multiple sites, wherein the method comprises π-π conjugated grafting of short nanofiber sponges with phosphorus-containing crown macromolecules containing multiple pyrrole groups to obtain a fiber sponge scaffold capable of capturing copper ions at multiple sites;
[0017] The short nanofiber sponge is prepared by electrospinning collagen and polylactic acid to obtain a three-dimensional porous scaffold, which is then cross-linked with glutaraldehyde.
[0018] In bone repair scaffold materials, there are generally high requirements for the mechanical properties of the scaffold. Based on this, the existing fiber sponge scaffold cannot be well applied to the repair of bone defects due to its poor mechanical properties. However, through a lot of exploration, the inventors unexpectedly discovered that by grafting phosphorus-containing crown macromolecules containing multiple pyrrole groups on the fiber sponge scaffold, after the scaffold captures copper ions in the body, it can significantly improve the mechanical properties of the fiber sponge scaffold. As shown in the examples, the initial Young's modulus of the fiber sponge scaffold provided by the present invention is significantly improved after capturing copper ions.
[0019] The phosphorus-containing crown macromolecule in the present invention is a phosphorus-containing crown macromolecule with a hydrophobic alkyl long chain prepared by substitution and condensation reaction with hexachlorocyclotrimer phosphazene as the core, and multiple pyrrole groups are modified on its surface. The inventor unexpectedly found that after the phosphorus-containing crown macromolecule is grafted with an electrospun short nanofiber sponge scaffold, the mechanical properties of the fiber sponge scaffold can be further improved, which well solves the defect that it cannot be used as a bone repair material.
[0020] The excellent mechanical properties of scaffold materials are of great significance for bone regeneration. First of all, most clinical bone defects are irregular, which requires the design of biomaterials of different shapes and sizes to fill the defect. Therefore, scaffold materials with good mechanical properties can just meet this requirement and can be prepared into different shapes and sizes according to different clinical needs, so as to provide individualized treatment for different patients. In addition, the bone defect needs the support of scaffold materials with certain mechanical properties to guide the formation of blood vessels and bone callus.
[0021] On the other hand, most of the current scaffold materials exert their osteogenic effects by exogenously adding copper ions. However, exogenously added copper ions, including copper ion-containing bioglass and copper ion-containing electrospun fiber membranes, generally show problems such as uncontrollable copper ion release rate and biosafety.
[0022] The nanofiber sponge scaffold provided by the present invention can not only improve the mechanical properties, but also actively capture the free Cu in the body at multiple sites. 2+ , thereby synergistically promoting bone regeneration. It avoids the possible safety issues of large-dose exogenous copper ions. At the same time, the fiber sponge scaffold can stably release the captured copper ions for a long time, which is more conducive to the formation of vascularization and the promotion of bone regeneration, and has an excellent effect on bone repair.
[0023] The electrospun short fiber sponge scaffold obtained by the present invention has good mechanical properties, water absorption, and biocompatibility through in vitro experiments, and can capture free copper ions at multiple sites and release copper ions continuously and stably, promoting the osteogenic differentiation of bone marrow mesenchymal stem cells and the formation of new blood vessels. Micro-CT and histological tests in vivo have verified that the electrospun short fiber scaffold with multiple copper ion capture sites has excellent biocompatibility, can promote angiogenesis in vivo and promote the repair of rat skull defects.
[0024] Furthermore, the weight ratio of the collagen to polylactic acid is 4:1.
[0025] Furthermore, the collagen is fish collagen.
[0026] Furthermore, the molecular weight of the polylactic acid is in the range of 30 to 50 kDa.
[0027] Furthermore, the collagen and polylactic acid are dissolved in hexafluoroisopropanol to prepare a spinning solution with a mass percentage of 10%.
[0028] Furthermore, the process parameters of the electrospinning are: voltage 18 kV, receiving distance 15 cm, and liquid feeding rate 3 mL / h.
[0029] Furthermore, the cross-linking time is 30 minutes.
[0030] Furthermore, the preparation method of the phosphorus-containing crown macromolecule is as follows: The preparation method of the phosphorus-containing crown macromolecule containing multiple pyrrole groups comprises the following steps:
[0031] 1) Add potassium carbonate to the tetrahydrofuran solution of hexachlorocyclotriphosphazene, add stearic acid amide tetrahydrofuran solution dropwise at low temperature, react at room temperature, filter, and vacuum dry to obtain C 17 -Ph-(N3P3)-Cl5;
[0032] 2) Add cesium carbonate to the tetrahydrofuran solution of p-hydroxybenzaldehyde, and then add the C obtained in step (1) dropwise. 17 -Ph-(N3P3)-Cl5 tetrahydrofuran solution, react at room temperature, filter, purify, and vacuum dry to obtain C 17 -Ph-(N3P3)-(Ph-CHO)5;
[0033] 3) In C 17 -Ph-(N3P3)-(Ph-CHO)5 dichloromethane solution was added with anhydrous sodium sulfate, and thiophosphoryl chloride modified with methylenehydrazine was added dropwise under ice bath condition, stirred at room temperature overnight, filtered, purified, and dried in vacuo to obtain C 17 -Ph-(N3P3)-(Ph-P-Cl2)5;
[0034] 4) In C 17 Potassium carbonate is added to the tetrahydrofuran solution of -Ph-(N3P3)-(Ph-P-Cl2)5, and the tetrahydrofuran solution of the pyrrole derivative HO-Ph-NC5 is added dropwise, stirred at room temperature overnight, rotary evaporated, purified, and vacuum dried to obtain the phosphorus-containing crown macromolecule containing multiple pyrrole groups.
[0035] The second object of the present invention is to provide a fiber sponge scaffold prepared by the method as described above, which can improve mechanical properties and capture copper ions at multiple sites.
[0036] The third object of the present invention is to provide an application of the fiber sponge scaffold as described above that can improve mechanical properties and capture copper ions at multiple sites, and to use the fiber sponge scaffold to prepare an implant material or a drug carrier that promotes bone repair.
[0037] The beneficial effects of the present invention are as follows:
[0038] (1) The present invention constructs a micro-nano electrospun short fiber sponge scaffold that can actively capture metal ions at multiple sites. The capture of copper ions by the fiber sponge scaffold can significantly improve the mechanical properties of the electrospun short fiber sponge scaffold, thus overcoming the problem of poor mechanical properties of existing fiber sponge scaffolds.
[0039] (2) The micro-nano electrospun short fiber sponge scaffold provided by the present invention can actively capture metal ions at multiple sites in the body, and can well replace the existing scaffolds that add exogenous metal ions. The scaffold of the present invention can stably release the captured copper ions for a long time. In vitro experiments have shown that the functional micro-nano short fiber sponge scaffold can capture copper ions at multiple sites, and the captured copper ions can be stably released for a long time, and the release time can be up to 21 days.
[0040] (3) The fiber sponge scaffold obtained by the present invention can promote the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) and promote angiogenesis. In vivo experiments have shown that the micro-nano short fiber sponge scaffold effectively promotes the regeneration of rat skull by promoting the formation of new blood vessels at the defect site and regulating the osteogenic differentiation of local BMSCs. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the preparation process of 3D NS@PD scaffolds, and the prepared 3D NS@PD scaffolds can capture free Cu at multiple sites 2+ , and through Cu 2+ It promotes the proliferation of endothelial cells to form blood vessels and the osteogenic differentiation of BMSCs, thereby achieving integrated repair of vascularization and three-dimensional bone regeneration.
[0042] Figure 2Preparation and characterization of different scaffold materials; (A) PD synthesis process; (B) Appearance pictures of different scaffolds; (C) Typical SEM images of each scaffold at different magnifications; (D) EDS detection of NS@PD scaffold; Nanofiber diameter (E) and porosity (F) of NF, NS and NS@PD scaffolds; (G) Fourier transform infrared spectroscopy (FTIR) detection results of different samples; Water absorption rate (H), expansion rate (I) and water absorption reversibility (J) of NS and NS@PD scaffolds.
[0043] Figure 3 Characterization of NS scaffolds; (A) HE staining of NS scaffolds and (B) phalloidin staining results.
[0044] Figure 4 To test the rapid and reversible water absorption of NS@PD scaffolds.
[0045] Figure 5 This is the elasticity test of the NS@PD scaffold. The NS@PD scaffold changes its shape under the action of external force and can quickly return to its original shape after the external force is removed.
[0046] Figure 6 Multi-site capture of Cu for NS@PD scaffolds 2+ Verification and capture of Cu 2+ The NS@PD@Cu(II) scaffold was then characterized; (A) NS@PD scaffold captures Cu 2+ Mechanism diagram; (B) Cu capture at different magnifications 2+ (C) SEM results of NS@PD@Cu(II) scaffolds; (C) surface roughness analysis of NS@PD and NS@PD@Cu(II) scaffolds; (D) EDS detection of NS@PD@Cu(II) scaffolds; water absorption rate (E), swelling rate (F), water absorption reversibility (G), mechanical properties (H), nanofiber diameter (I) and porosity (J) of NS@PD and NS@PD@Cu(II) scaffolds; (K) contents of different elements on NS@PD@Cu(II) scaffolds; (L) release curve of copper ions from NS@PD@Cu(II) scaffolds.
[0047] Figure 7 The mechanical properties characterization results of NS@PD scaffold and NS@PD@Cu(II) scaffold.
[0048] Figure 8 This is the copper ion release curve of NS@PD@Cu(II) scaffold.
[0049] Fig. 9Effects of different scaffolds on the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs); (A) Schematic diagram of the effects of scaffolds on the proliferation and osteogenic differentiation of BMSCs; (B) Live / dead staining and (C) phalloidin staining on days 1, 3, and 5 after co-culture of scaffold extracts with BMSCs; (D) SEM observation of the growth of BMSCs on NS, NS@PD, and NS@PD@Cu(II) scaffolds; (E) Immunofluorescence staining to observe the expression of BMP-2 in different groups; (F) HE staining to observe the growth of BMSCs on NS, NS@PD, and NS@PD@Cu(II) scaffolds; (G) ALP staining and (H) Alizarin red staining; (I) Live / dead cell staining statistics; (J) CCK-8 results; (K) RT-PCR detection of the expression of BMP-2 and Col-I mRNA in different groups; (L) Quantitative analysis of immunofluorescence staining; (M) ALP quantitative analysis results and (N) Alizarin red staining quantitative analysis results.
[0050] Fig.10 The following are general images of ALP staining of the scaffolds in each group on the seventh day.
[0051] Fig.11 Effects of different scaffolds on HUVECs proliferation and angiogenesis; (A) Schematic diagram of the effects of various scaffolds on HUVECs proliferation and angiogenesis; (B) Live / dead staining results on days 1, 3, and 5 after co-culture of HUVECs with different scaffold extracts; (C) Tubule formation after HUVECs were treated with different scaffold extracts; (D) Phalloidin staining; (E) SEM detection and (F) HE staining to observe the growth of HUVECs on different scaffolds; (G) Immunofluorescence staining to observe the expression of CD-31 in different groups; (H) Live and dead cell staining statistics; (I) CCK-8 results; (J), (K), and (L) are quantitative analyses of tubule formation (total length and number of junctions); (M) Quantitative analysis of immunofluorescence staining.
[0052] Fig.12 Effects of different scaffolds on bone regeneration in vivo; (A) Schematic diagram of the in vivo experimental process; (B) Mic-CT three-dimensional reconstruction images of the bone defect area 4 weeks and (C) 8 weeks after surgery; (D) quantitative analysis results of bone mineral density (BMD), (E) bone volume fraction (BV / TV), (F) trabecular number (Tb.N) and (G) trabecular thickness (Tb.Th) (statistical analysis was performed using two-way ANOVA followed by Tukey's multiple comparison test; #, &, * indicate statistical differences compared with the control group, NS@PD group and NS@PD@Cu(II) group, respectively, p<0.05).
[0053] Fig.13HE staining and Masson's staining of different scaffolds; (A) HE staining results at different magnifications 4 and 8 weeks after surgery; (B) Masson's staining results at different magnifications 4 and 8 weeks after surgery; (C) Quantitative analysis results of new bone formation; (D) The proportion of mature bone tissue (#, &, * indicate statistical differences compared with the control group, NS@PD group and NS@PD@Cu(II) group, respectively, p<0.05).
[0054] Fig.14 Immunohistochemical staining of CD-31 and OPN on different scaffolds; (A) CD-31 immunohistochemical staining at different magnifications 4 and 8 weeks after surgery; (B) OPN immunohistochemical staining at different magnifications 4 and 8 weeks after surgery; (C) Quantitative analysis results of the relative positive areas of CD-31 and (D) OPN (#, &, * indicate statistical differences compared with the control group, NS@PD group and NS@PD@Cu(II) group, respectively, p<0.05).
[0055] Fig.15 CD-31 immunofluorescence staining; (A) CD-31 immunofluorescence staining results at different magnifications at 4 weeks and (B) 8 weeks after surgery; (C) relative positive areas of CD-31 immunofluorescence staining at 4 weeks and (D) 8 weeks (#, &, * indicate statistical differences compared with the control group, NS@PD group and NS@PD@Cu(II) group, respectively, p<0.05). DETAILED DESCRIPTION
[0056] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0057] Example 1
[0058] (I) Preparation of electrospun short fiber sponge scaffolds with improved mechanical properties and multi-site capture of copper ions:
[0059] The preparation process of electrospun short fiber scaffolds with improved mechanical properties and multi-site capture of copper ions (denoted as 3D NS@PD) is as follows: Figure 1 As shown, the main steps include electrospinning, nanofiber homogenization, glutaraldehyde cross-linking molding, and modification of phosphorus-containing crown macromolecules.
[0060] The specific preparation method of the 3D NS@PD scaffold is as follows:
[0061] (1) Preparation of nanofiber membrane:
[0062] A mixture of 1g of fish collagen and polylactic acid (PLA, molecular weight 50kDa) (mass ratio 80:20) was dissolved in 10ml HFIP (hexafluoroisopropanol), stirred at room temperature until completely dissolved, and a spinning solution with a concentration (mass) of 10% was prepared. The spinning solution was injected into a 10ml syringe for electrospinning, and the parameters were set as follows: voltage 18kV, receiving distance 15cm, liquid feeding rate 3mL / h, and PLA / Col electrospun nanofiber membrane (abbreviated as NF) was prepared;
[0063] (2) Preparation of short nanofiber sponge scaffolds:
[0064] The prepared PLA / Col electrospun nanofiber membrane was cut into small fragments, and the cut nanofiber fragments were evenly dispersed in tert-butyl alcohol using a high-speed homogenizer, with the speed set to 10,000 rpm and the time set to 30 min. The broken short fiber liquid was injected into a 48-well plate and a 24-well plate respectively and freeze-dried for 24 hours to remove the tert-butyl alcohol, obtaining a three-dimensional scaffold with a porous structure, which was a non-cross-linked short nanofiber sponge scaffold.
[0065] Subsequently, glutaraldehyde (1.5 mL) was used for cross-linking for 30 min, and the cross-linked scaffold was added to a 0.5 M hydrochloric acid solution containing 5 wt % glutamic acid to soak and remove the glutaraldehyde, and then freeze-dried to obtain a cross-linked short nanofiber sponge scaffold, which was recorded as a 3D NS scaffold (abbreviated as NS);
[0066] (3) Phosphorus-containing crown macromolecules (abbreviated as PD) containing multiple pyrrole groups were grafted onto the above-mentioned short nanofiber sponge scaffold through π-π conjugation to obtain electrospun short fiber sea scaffolds with multi-site copper ion capture, which were recorded as 3D NS@PD scaffolds (abbreviated as NS@PD).
[0067] The synthetic route of the phosphorus-containing crown macromolecule PD containing multiple pyrrole groups is shown in Figure 2 Part A, the specific preparation method is as follows:
[0068] 1) Potassium carbonate (34.5 mmol) was added to 50 mL of hexachlorocyclotriphosphazene tetrahydrofuran solution (0.345 M), and then 10 mL of stearic acid amide tetrahydrofuran solution (1.725 M) was added dropwise at -61 °C. The mixture was reacted at room temperature for 12 hours, and the supernatant was filtered and dried in vacuum to obtain C 17 -Ph-(N3P3)-Cl5;
[0069] 2) Add cesium carbonate (172.5 mmol) to 50 mL of p-hydroxybenzaldehyde tetrahydrofuran solution (0.379 M), and then add 25 mL of C 17-Ph-(N3P3)-Cl5 tetrahydrofuran solution (0.138M) was reacted at room temperature for 12 hours, the supernatant was filtered and rotary evaporated to 10 mL, and then added dropwise to 100 mL of pentane, stirred for 0.5 hours, and the supernatant was removed and vacuum dried to obtain C 17 -Ph-(N3P3)-(Ph-CHO)5;
[0070] 3) In 50mL C 17 Anhydrous sodium sulfate (4.2 mmol) was added to a dichloromethane solution (0.007 M) of -Ph-(N3P3)-(Ph-CHO)5, and thiophosphoryl chloride (1.925 mmol) modified with methylenehydrazine was added dropwise under ice bath conditions. The mixture was stirred at room temperature overnight, and the supernatant was filtered and rotary evaporated to 10 mL. The mixture was added dropwise to 100 mL of pentane and stirred for 0.5 h. The supernatant was removed and dried in vacuo to obtain C 17 -Ph-(N3P3)-(Ph-P-Cl2)5;
[0071] 4) In 25 mL C 17 -Ph-(N3P3)-(Ph-P-Cl2)5 tetrahydrofuran solution (0.005M) was added with potassium carbonate (1.875mmol), and 2.5mL of pyrrole derivative HO-Ph-NC5 tetrahydrofuran solution (0.55M) was added dropwise, and stirred at room temperature overnight. The mixture was rotary evaporated to 10mL, and added dropwise to a mixed solution of 100mL of pentane and ethyl acetate (v:v=1:1), and stirred for 0.5h. The supernatant was removed and dried in vacuo to obtain PD.
[0072] (II) 3D NS@PD scaffolds for Cu 2+ The catch:
[0073] The 3D NS@PD scaffold was placed in a CuCl2 solution and incubated at 37°C. Samples were taken at different time points. The scaffold after capturing copper ions was defined as a 3D NS@PD@Cu(II) scaffold, abbreviated as NS@PD@Cu(II).
[0074] Test method example
[0075] 1. Physical characterization of the stent
[0076] The prepared scaffolds were photographed and observed by a digital camera, and their microstructures were observed by a scanning electron microscope. The distribution of elements on different scaffolds was determined by energy spectrum analysis. The scaffolds were characterized by infrared, and the hydrophilicity, porosity, water absorption, swelling rate, and mechanical properties of the scaffolds were tested. The specific characterization methods are as follows:
[0077] (1) The porosity of two-dimensional nanofiber membrane (NF), 3D NS scaffold (NS), 3D NS@PD scaffold (NS@PD) and 3D NS@PD@Cu(II) scaffold (NS@PD@Cu(II)) was tested by liquid immersion method. The specific method is as follows: NF, NS, NS@PD and NS@PD@Cu(II) were weighed and recorded as M1 (g), immersed in acetone solution, and the corresponding scaffold weight in wet state was weighed after 48 hours and recorded as M2 (g).
[0078] The porosity (%) was calculated according to the following formula:
[0079] Porosity (%) = (M2-M1) / ρV.
[0080] ρ(g / cm 3 ) is the density of acetone, V (cm 3 ) is the volume of the support.
[0081] (2) The water absorption rate and expansion rate of the scaffold were tested. The specific method is as follows: first, the weight and volume of the dry scaffold were weighed, which are W1 and V1 respectively. Then, the scaffold was soaked in deionized water for 0, 1, 3, 5, 10, 20, and 30 minutes respectively, and the wet weight (W2) and volume (V2) of the scaffold were weighed again.
[0082] The water absorption rate and expansion rate of the scaffold were calculated according to the following formula:
[0083] Water absorption rate = (W2-W1) / W1×100%;
[0084] Expansion rate = (V2 - V1) / V1 x 100%.
[0085] (3) The mechanical properties of the scaffolds were tested using a compression test machine. The specific steps are as follows: NS, NS@PD and NS@PD@Cu(II) were soaked in deionized water to make them fully wetted, and then compression cycle tests were performed on each scaffold according to the set compression conditions. After the scaffold deformation reached 80%, the deformation was restored to 0%, and this cycle was repeated 20 times to obtain the final compression cycle mechanical test graph, which was further analyzed to obtain the maximum compressive stress and Young's modulus.
[0086] 2. Testing the ability of the scaffold to capture copper ions at multiple sites in vitro
[0087] In order to verify that the 3D NS@PD scaffold has the function of capturing copper ions, its ability to capture copper ions in vitro was first verified.
[0088] The 3D NS@PD@Cu(II) scaffold was characterized by SEM, surface roughness analysis, energy spectrum analysis, and inductively coupled plasma atomic emission spectroscopy (ICP-OES). The mechanical properties of the scaffold were tested. Finally, the release of copper ions from the 3D NS@PD@Cu(II) scaffold was tested.
[0089] The specific method is as follows: 100 mg of 3D NS@PD@Cu(II) scaffold was placed in deionized water and incubated at 37°C. 500 μL of samples were taken at different time points, and an equal volume of fresh deionized water was added at the same time. The Cu(II) concentration in the solution was determined by ICP-OES, and the cumulative release percentage of Cu(II) was plotted as a function of release time.
[0090] 3. Cytocompatibility test
[0091] BMSCs and HUVECs were selected to verify the cell compatibility of different scaffold materials. Since the scaffold materials easily absorb the color of the dye and are not conducive to observing the morphology of cells, the cell experiment verified the interaction between the scaffold and the cells through the scaffold extract.
[0092] BMSCs and HUVECs were cultured at 8.0×10 3 The cells were inoculated into the culture plate at a density of 100 μL / well and placed in an incubator for culture at 37°C and a CO2 concentration of 5%. The medium (complete culture medium containing scaffold extract) was changed every other day. On the 1st, 3rd and 5th day after culture, the cells in each group were stained for live and dead cells and tested for CCK-8. The steps are as follows: 250 μL of CalceinAM / PI detection working solution (Biyuntian, China) was added to each well, incubated for 30 minutes and observed under a fluorescence microscope. After adding 10 μL of CCK-8 solution to each well of the 96-well plate, the absorbance value was measured at 450 nm by a FlexStaston3 microplate reader (Molecular Devices, Japan) after incubation at 37°C for 1 hour.
[0093] In addition, the growth and penetration of cells in the scaffold were verified by SEM and phalloidin staining. The specific steps are as follows: BMSCs and HUVECs cells were co-cultured with different scaffolds for 5 days, fixed with 4% paraformaldehyde at 4°C, dehydrated with alcohol gradient, then embedded and paraffin sectioned. After sectioning, phalloidin staining was performed to observe the penetration and growth of cells in the scaffold. The dehydrated samples were dried at the critical point of carbon dioxide, and the growth of cells on the scaffold was observed by SEM after gold spraying.
[0094] 4. In vitro osteogenic differentiation experiment
[0095] The in vitro osteogenic ability of the scaffold was detected by alkaline phosphatase (ALP) staining, alizarin red staining, immunofluorescence staining and RT-PCR. The specific steps are as follows:
[0096] BMSCs were seeded into 24-well plates and cultured in DMEM / F12 medium containing 10% fetal bovine serum (complete medium containing scaffold extract). When the cells were about 60% confluent, the medium was replaced with osteogenic medium (Cyagen, China). After 7 days of culture, ALP was detected and quantified for each group of cells. After 21 days, the calcium nodules were stained with alizarin red, and then dissolved with perchloric acid for quantitative analysis.
[0097] In addition, after 21 days of culture, the osteogenic differentiation effect of each group was observed by BMP-2 immunofluorescence staining, and each group was extracted. The osteogenic-related genes of each group were detected by real-time fluorescence quantitative PCR (RT-qPCR). First, the total RNA of each group of cells was extracted using an RNA extraction kit (Takara, Japan), and then the extracted RNA was reverse transcribed into cDNA using a reverse transcription kit (Takara, Japan). qRT-PCR detection was performed using the power SYBR green RT-PCR kit. The reference gene was GAPDH, and the primer sequences corresponding to all genes are shown in Table 1. Gene expression was analyzed by the 2-ΔΔCt method.
[0098] Table 1 Primer sequences used for RT-PCR detection
[0099]
[0100] 5. In vitro angiogenesis assay
[0101] The in vitro angiogenesis ability of the scaffold was tested by the small tube test. HUVECs were cultured at 3×10 4 The cells were inoculated into a 24-well confocal dish at a density of 100 cells / well, and then co-cultured with the complete medium containing the scaffold extract. After culturing for 4 and 6 hours, the formation of the tubes was observed by Calcein AM staining, and then photographed and recorded. The number of meshes, number of junctions and the total tube length were analyzed by Image J software.
[0102] 6. In vivo experiments
[0103] The corresponding animal experiments were approved by the Ethics Committee of Chongqing Medical University [2022-K304]. A total of 24 SD rats were used in this experiment (male, average weight 300-350g). Establishment of rat skull defect model: Rats were anesthetized by intraperitoneal injection of pentobarbital, and the skin was incised after skin preparation to expose the skull, and a skull defect with a diameter of 4mm was prepared with an oral drill. The experiment was divided into 4 groups, namely: control group (n=6), Fiber group (n=6), NS group (n=6), and NS@PD (n=6). After different treatments were performed in each group, the skin was sutured and disinfected again, and penicillin was continuously injected after surgery to prevent infection.
[0104] 7. Mic-CT
[0105] At 4 and 8 weeks after surgery, the rats in each group were examined by Mic-CT (SkyScan, SkyScan 1176, Belgium) to evaluate the regeneration of the rat skull. The parameters were as follows: 65 kV, 385 mA, 1 mm Al filter. The scanning results were reconstructed in three dimensions using Mimic software.
[0106] 8. Histological analysis
[0107] The rats were killed at 4 and 8 weeks after surgery, and the entire skull was removed. The skull specimens were fixed with 4% paraformaldehyde, then decalcified, embedded, sliced, and stained. The skull regeneration in each group was evaluated by HE staining and Masson staining. Immunohistochemical staining of CD-31 and OPN was then performed to observe the neovascularization and bone regeneration in each group. The relative expression levels of CD-31 and OPN were determined using Image J software.
[0108] Experimental results example 1
[0109] 1. Performance of electrospun short fiber sea scaffold
[0110] The nanofiber membrane (NF), 3D NS scaffold (NS) and 3D NS@PD scaffold (NS@PD) prepared in Example 1 were generally observed and photographed with a digital camera.
[0111] like Figure 2 As shown in part B: NF is in the form of a white film. After the nanofiber membrane (NF) is cut into pieces, it can be evenly dispersed in tert-butanol, and the NS scaffold is a white three-dimensional structure.
[0112] Then, the microstructures of different scaffolds were observed by SEM. Figure 2As shown in the middle C part: the surface of the NF nanofibers is smooth and arranged in disorder. The NS scaffold is composed of a large number of broken nanofibers, and micropores of different sizes and irregular shapes are randomly distributed between the fibers. From the SEM images of different magnifications, it can be seen that the NS scaffold and the NS@PD scaffold are both composed of a large number of broken nanofibers. This structure can well simulate the natural ECM and is conducive to cell adhesion and growth. More importantly, the main component of the 3D scaffold is fish collagen, which is mainly composed of type I collagen, which is very similar to the composition of bone tissue. Therefore, the scaffold simulates the natural ECM well in both structure and composition. In addition, type I collagen, the main product after the degradation of the scaffold, can promote differentiation and cell adhesion of osteoblasts through integrins, and play an important role in the metabolic growth of cells.
[0113] The SEM images also showed that the surface of the NS scaffold was smooth. After modification with PD, the surface of the NS@PD scaffold became rough, which confirmed that PD was successfully grafted onto the NS scaffold and that the original structure of the NS scaffold was not changed after grafting with PD ( Figure 2 (Part C).
[0114] In addition, the EDS test results showed that the P element was evenly distributed on the surface of the NS@PD scaffold, proving that PD was successfully grafted onto the NS scaffold ( Figure 2 Further analysis of the fiber diameter shows that the diameter of the NS@PD scaffold is larger than that of the NF nanofiber membrane and the NS scaffold, which indirectly proves that the NS scaffold has been successfully grafted with PD. Figure 2 As can be seen in part E, there is no significant difference in the diameter of the NF nanofiber membrane and the NS scaffold. The results of Fourier transform infrared spectroscopy (FTIR) also show that PD was successfully modified onto the NS scaffold ( Figure 2 (see Section G in the Appendix).
[0115] The porosity of scaffold materials is one of the key indicators for evaluating scaffold materials. It is a prerequisite for cell growth, nutrient transport and exchange. Therefore, the porosity of the scaffold was measured by liquid immersion method. The results showed that the porosity of NF nanofiber membrane, NS scaffold and NS@PD scaffold were 64.5%, 93.37% and 85.94%, respectively. Figure 2 (Part F in the middle). Although the porosity of the NS@PD scaffold was slightly reduced after grafting PD, it still had a high porosity and could well meet the requirements of cell growth and nutrient exchange.
[0116] The water absorption rate of the scaffold is another important indicator of the scaffold. A scaffold with high water absorption rate can provide nutrients to cells well. Therefore, the water absorption rate of the scaffold was tested.
[0117] like Figure 2As shown in Parts H and I, all 3D scaffolds reached their maximum water absorption and expansion rates within 1 min after contact with water. The maximum water absorption and expansion rates of NS scaffolds and NS@PD scaffolds were different. The maximum water absorption and expansion capacity of NS scaffolds were higher than those of NS@PD scaffolds, which was related to the different porosities of different scaffolds ( Figure 2 In addition, the water absorption of the scaffolds is reversible, and when these scaffolds are compressed at a strain of 80%, most of the adsorbed water can be removed. When the compression force is released, these scaffolds will absorb water again after being immersed in water and return to their original shape. After 5 compression cycles, the maximum water absorption rate of the scaffolds did not change significantly and still had high water absorption, indicating that the water absorption of the scaffolds is reversible ( Figure 2 The strong water absorption performance of the scaffold material has a unique advantage in tissue repair. It can not only stop bleeding locally, but also prevent local infection caused by a large amount of exudate.
[0118] Further HE staining and phalloidin staining of the NS scaffold showed that the NS scaffold was composed of a large number of short fibers with relatively uniform diameters, proving that the short fiber scaffold prepared by this method had a uniform structure ( Figure 3 Part A and Part B).
[0119] In addition, the PD-modified NS@PD scaffold has good elasticity and can still maintain its original shape after external force ( Figure 4 ).
[0120] In addition, when the NS scaffold and NS@PD scaffold were exposed to water, they could quickly absorb water and reach the maximum water absorption and expansion within 1 minute ( Figure 5 ).
[0121] The above test results all prove that the present invention successfully prepared a 3D NS@PD scaffold, which is composed of a large number of uniform short fibers and can well simulate the structure of natural ECM. 2. Capture effect of the scaffold on free copper ions
[0122] At present, copper ion-based biomaterials mainly use exogenous copper ions to transport them into the body through specific carriers for bone repair. Exogenous copper ion addition has disadvantages such as uncontrollable dosage and easy to cause toxic reactions. The stent designed by the present invention can actively capture copper ions at multiple sites, which is impossible to achieve with the prior art.
[0123] The process of NS@PD scaffold capturing copper ions is shown in Figure 6 As shown in part A. SEM scanning shows that the surface of NS@PD@Cu(II) is very rough and has a large amount of particle deposition, proving that copper ions have been successfully captured ( Figure 6 (Part B).
[0124] The surface roughness of the stent was further analyzed, and the results were as follows: Figure 6 As shown in part C: the surface roughness of NS@PD@Cu(II) is significantly higher than that of NS@PD, proving that NS@PD successfully captured copper ions.
[0125] Next, EDS detection was used to further verify the capture effect of NS@PD scaffold material on copper ions. EDS results showed that the NS@PD@Cu(II) scaffold had copper element distribution, proving that the NS@PD scaffold can capture copper ions ( Figure 6 (section D).
[0126] The NS@PD@Cu(II) scaffold after capturing copper ions was further characterized. The results showed that the water absorption rate, expansion rate and porosity of the NS@PD@Cu(II) scaffold were lower than those of NS@PD. The main reason was that the captured copper ions occupied the space of the scaffold, thus reducing the water absorption rate, expansion rate and porosity of the scaffold ( Figure 6 E, F and J of the .
[0127] The mechanical properties of biomaterials are crucial to their biological properties and applications. Different tissues have different requirements for the mechanical properties of scaffold materials. Therefore, designing bioscaffold materials that can match the mechanical properties required by specific tissues is of great significance for tissue repair. Studies have shown that electrospun membranes of different stiffness play a decisive role in the differentiation and function of mesenchymal stem cells (MSCs). MSCs cultured on matrices with stiffness similar to that of brain, muscle or bone tissue will preferentially become neurons, muscle or osteoblasts, respectively. Therefore, the mechanical properties of the scaffold materials were further tested.
[0128] like Figure 7 ( Figure 6 As shown in the enlarged view of part H in the figure, the NS@PD scaffold can still recover and maintain good shape and mechanical properties after being compressed 20 times. The initial Young's modulus is 0.39MPa, and the Young's modulus remains at 0.25MPa after being compressed 20 times.
[0129] The initial Young's modulus of the NS@PD@Cu(II) scaffold is 0.52MPa, and the Young's modulus remains at 0.37MPa after 20 compressions. It can be seen that the mechanical properties of the NS@PD@Cu(II) scaffold are significantly better than those of the NS@PD scaffold.
[0130] From the above results, it can be seen that in addition to actively capturing free copper ions, the NS@PD scaffold also further improves the mechanical properties of the fiber sponge scaffold.
[0131] These results indicate that the 3D NS@PD scaffolds capture Cu2+ The mechanical properties of the stent can be significantly improved, and this property determines that the stent can still maintain its original shape when subjected to external forces.
[0132] Finally, the Cu 2+ Release was tested. Figure 8 (for Figure 6 As shown in the enlarged view of part L in the figure, the Cu captured by the NS@PD@Cu(II) scaffold 2+ The release can be stable and last for more than 21 days. This result shows that the scaffold obtained by the present invention can not only actively capture Cu 2+ In addition to further improving the mechanical properties of the sponge scaffold, it can also stably release Cu for a long time. 2+ This property is extremely important for the repair of bone damage and can better promote bone regeneration and repair.
[0133] 3. Effects of scaffolds on proliferation and osteogenic differentiation of BMSCs
[0134] Stem cells are currently widely used in the field of tissue regeneration and are of great significance to tissue regeneration. In the field of bone regeneration, bone marrow mesenchymal stem cells (BMSCs) are involved in the repair of bone tissue and are currently widely used. Good biocompatibility of scaffold materials is a prerequisite for their application in vivo, so the biocompatibility of different scaffolds was tested.
[0135] The experimental process is as follows Fig. 9 As shown in part A of the figure. The live and dead cell staining results showed that the number of cells in each group increased with the extension of culture time, and there was no difference in the number of live cells in each group on the 1st, 3rd and 5th days, proving that the scaffold had no toxicity to cells ( Fig. 9 The CCK-8 results also further proved that the scaffold was non-toxic ( Fig. 9 (see Section J in the figure).
[0136] On the 5th day of culture, the BMSCs on the scaffolds were stained with phalloidin, HE and SEM ( Fig. 9 The results of phalloidin staining and HE staining showed that BMSCs could grow into the NS scaffold, NS@PD scaffold and NS@PD@Cu(II) scaffold along the pores of the scaffold, modify PD on the NS scaffold and capture Cu 2+ There was no effect on cell growth ( Fig. 9 The SEM results also show that BMSCs can grow on the surface of the scaffold and grow into the scaffold along the pores of the scaffold, and the formation of extracellular matrix can be seen ( Fig. 9In addition, it can be seen that BMSCs can also grow well on the NF nanofiber membrane ( Fig.10 ).
[0137] The effects of different scaffolds on the osteogenic differentiation of BMSCs were verified by alkaline phosphatase (ALP) staining, alizarin red staining, immunofluorescence staining, and real-time fluorescence quantitative PCR (RT-PCR) detection. First, after co-culturing the extracts of different scaffolds with BMSCs for 7 days, the early osteogenic properties of different scaffolds were verified by ALP staining. Fig. 9 Part G, Part M and Fig.10 As shown in the figure, the NS@PD@Cu(II) scaffold expressed more ALP than the NS scaffold and NS@PD scaffold, indicating that the captured copper ions can promote the osteogenic differentiation of BMSCs.
[0138] At 21 days of culture, the late osteogenic effects of different scaffolds were further verified by alizarin red staining. The results were consistent with ALP: the NS@PD@Cu(II) scaffold group had more calcium nodules than the NS scaffold and NS@PD scaffold groups, and was more able to promote the osteogenic differentiation of BMSCs ( Fig. 9 H and N parts).
[0139] Subsequently, BMP-2 immunofluorescence staining and semi-quantification were performed to further evaluate the effects of different scaffolds on the osteogenic differentiation of BMSCs. The results showed that the NS@PDCu(II) group had more fluorescence expression than the NS group and NS@PD group, indicating that it had better osteogenic potential ( Fig. 9 E and L parts).
[0140] Finally, RT-PCR was used to evaluate the expression levels of two genes, bone morphogenetic protein (BMP-2) and type I collagen (Col-I). Fig. 9 As shown in part K, it can be seen that the expression of BMP-2 and Col-I in the NS@PDCu(II) scaffold group is higher than that in other groups.
[0141] 4. Effects of scaffolds on HUVECs proliferation and angiogenesis
[0142] Currently, most of them are based on doped Cu 2+ The bone repair biomaterials are directly Cu 2+ Direct mixing with various biomaterials has problems such as too fast release and biosafety. Therefore, this section conducts in vitro experiments on the NS@PD scaffold that can actively capture copper ions constructed in the embodiment to verify its effect of capturing copper ions and the angiogenesis ability of the NS@PDCu(II) scaffold ( Fig.11 (Part A).
[0143] First, the cytocompatibility of various scaffolds with HUVECs was observed by live-dead cell staining. Fig.11 As shown in the figure, with the extension of culture time, the number of HUVECs cells gradually increased, but there was no statistical difference in the number of live cells in the NS, NS@PD and NS@PDCu(II) groups at 1 day, 3 days and 5 days, indicating that these three scaffolds have good cell compatibility and are non-toxic to HUVECs ( Fig.11 CCK-8 assay also confirmed that each scaffold had good cell compatibility, and there was no statistical difference in the number of HUVECs in each group at different time points ( Fig.11 Part I).
[0144] Then, the growth of HUVECs on each group of scaffolds was observed by SEM. Fig.11 As shown in the figure: HUVECs can grow on the surface of the scaffold and secrete a large amount of extracellular matrix, indicating that the scaffold provides a good spatial environment for the growth of HUVECs ( Fig.11 Part E in the middle). Phalloidin staining and HE staining further confirmed that HUVECs were able to grow on the scaffold and grow into the interior of the scaffold along the pores of the scaffold ( Fig.11 D and F of the .
[0145] The above experimental results all show that the NS scaffold, NS@PD scaffold and NS@PD@Cu(II) scaffold have good cell compatibility with HUVECs cells and HUVECs can grow well on the scaffold. It can be seen that the scaffold grafted with PD and captured Cu 2+ The biological characteristics of HUVECs were not changed, and they could still provide a suitable space environment for the growth of HUVECs.
[0146] The ability of bone repair biomaterials to induce angiogenesis plays a key role in the bone repair process, because new blood vessels can provide blood supply to tissues and deliver nutrients and oxygen to damaged areas, thereby accelerating the repair of bone damage. Therefore, the ability of different scaffolds to induce angiogenesis was verified by in vitro tubule formation experiments. Fig.11 As shown: At 3 hours and 6 hours, a large number of tubular structures can be seen in the NS@PD@Cu(II) scaffold group, while only a small number of vascular-like structures can be seen in the other groups ( Fig.11 The tubule formation was further analyzed by Image J. Fig.11The results of parts J, K, and L all showed that the angiogenesis in the NS@PD@Cu(II) scaffold group was significantly higher than that in the other groups. Finally, the effects of these scaffolds on angiogenesis were evaluated by immunofluorescence staining and semi-quantification of CD-31. The results showed that the fluorescence expression in the NS@PDCu(II) scaffold was stronger than that in the other groups ( Fig.11 G and M in the.
[0147] All these results indicate that the NS scaffold, NS@PD scaffold and NS@PD@Cu(II) scaffold have good biocompatibility with HUVECs, and the captured Cu 2+ Can induce HUVECs to form new blood vessels.
[0148] 5. In vivo experimental results
[0149] In vitro experiments demonstrated that the NS@PD scaffold can capture free Cu at multiple sites. 2+ And has good biocompatibility, in addition, the scaffold captures Cu 2+ It can promote the osteogenic differentiation of BMSCs and promote angiogenesis. 2+ The concentration of Cu was grafted on some sites of the NS@PD scaffold. 2+ , so that it can maintain local Cu 2+ concentration, and the remaining sites can capture free Cu in the body at multiple sites 2+ Thus maintaining Cu 2+ Maintaining it at physiological concentration is beneficial to the repair of bone damage.
[0150] By constructing a rat skull defect model, the scaffold's ability to promote osteogenesis and angiogenesis in vivo was studied to investigate the effect of the scaffold on skull injury repair. All animal operation procedures were approved by the Ethics Committee of Chongqing Medical University. At 4 and 8 weeks after surgery, the skull defect repair was tested ( Fig.12 First, Mic-CT scanning was performed on the specimens of each group to observe the bone regeneration in each group. Fig.12 As shown in Parts B and C, the NS@PD@Cu(II) scaffold group had significantly more new bone formation than the other groups at 4 and 8 weeks. In addition, the NS group and NS@PD group had more new bone formation than the control group, which may be related to the following reasons: on the one hand, the NS and NS@PD scaffolds can act as a local barrier to prevent the surrounding fibrous tissue from entering the bone defect site; on the other hand, the NS and NS@PD scaffolds are truly 3D scaffolds that can well mimic natural ECM and provide a good microenvironment for cell growth and tissue regeneration.
[0151] At 4 weeks, new bone formation in the NS@PD group was less than that in the NS@PD@Cu(II) group, which was mainly due to the Cu 2+ The presence of Cu(II) accelerated bone regeneration. In addition, the NS@PD group had more new bone formation than the NS group. At week 8, although the bone regeneration effect of the NS@PD group was not as good as that of the NS@PD@Cu(II) group, most of the bone defects in this group were filled with new bone. This may be because the NS@PD scaffold can capture Cu(II) at multiple sites in vivo. 2+ To promote bone regeneration.
[0152] Further three-dimensional reconstruction and analysis of bone volume fraction (BV / TV), bone mineral density (BMD), trabecular number (Tb.N) and trabecular thickness (Tb.Th) showed that the BV / TV, BMD, Tb.N and Tb.Th values of the NS@PD@Cu(II) group were significantly higher than those of the other groups, whether at the 4th or 8th week, indicating that the bone repair effect of the NS@PD@Cu(II) group was better than that of the other groups ( Fig.12 DG part).
[0153] The repair effect of different scaffolds on skull regeneration was further verified by histological examination. At 4 and 8 weeks after surgery, the specimens of each group were stained with HE and Masson's staining. Fig.13 As shown in the figure, it can be seen that the stents in each group were completely degraded 8 weeks after surgery, and no obvious inflammatory reaction or necrosis was observed in each group. Fig.13 As shown in part A, at the 4th and 8th weeks, a large amount of new bone was formed in both the NS@PD@Cu(II) group and the NS@PD group, while only a small amount of new bone was formed in the NS group and the control group. Obvious bone defects were observed in the control group, and the defects were filled with only a large amount of fibrous tissue.
[0154] Masson's staining results showed that the NS@PD@Cu(II) and NS@PD groups had more mature collagen deposition, indicating that the bone repair effect of NS@PD@Cu(II) and NS@PD scaffolds was better than that of other groups ( Fig.13 Further quantitative analysis of HE staining and Masson's staining showed that the NS@PD@Cu(II) and NS@PD groups had more new bone formation and more mature collagen deposition, which was statistically significant compared with the NS@PD@Cu(II) and NS@PD groups ( Fig.13 The results of histological examination showed that the bone repair effect of NS@PD@Cu(II) scaffold was significantly better than that of other groups, followed by NS@PD scaffold, which was consistent with the results of Mic-CT.
[0155] In order to further verify the angiogenic and osteogenic potential of the scaffold in vivo, immunohistochemical staining of CD-31 and Osteopontin (OPN) was performed respectively. Platelet endothelial cell adhesion molecule-1 (PECAM-1 / CD31) is a member of the immunoglobulin superfamily, expressed by endothelial cells, mediates intercellular adhesion, and is widely used to evaluate angiogenesis in vivo. The NS@PD@Cu(II) scaffold group showed better angiogenic ability 4 weeks after surgery, and the number of new blood vessels was higher than that of other groups. However, at 8 weeks after surgery, the number of blood vessels decreased compared with that at 4 weeks ( Fig.14 This phenomenon may be related to the peak time of angiogenesis, which reaches its peak 2 weeks after surgery and then begins to gradually decrease.
[0156] As one of the bone formation indicators, OPN can well evaluate the effect of bone formation in vivo, so immunohistochemical staining of OPN was performed. Fig.14 As shown in Part B, the OPN expression in the NS@PD@Cu(II) and NS@PD scaffold groups was significantly higher than that in the other groups, proving that the osteogenesis ability of these two groups was superior to that of the other groups. Quantitative analysis of the expression of CD-31 and OPN also showed that the expression of CD-31 and OPN in the NS@PD@Cu(II) and NS@PD scaffold groups was higher than that in the other scaffold groups, indicating that these two scaffolds have better angiogenesis and osteogenesis potential ( Fig.14 C and D).
[0157] In addition, immunofluorescence staining was used to further evaluate the angiogenesis of the scaffolds, and the results were consistent with those of immunohistochemistry staining, indicating that the NS@PD@Cu(II) and NS@PD scaffold groups had better angiogenesis potential ( Fig.15 ).
[0158] The in vivo evaluation results of Mic-CT detection, HE staining, Masson staining, immunohistochemistry staining and immunofluorescence staining all proved that NS@PD@Cu(II) and NS@PD scaffolds have better bone repair therapeutic effects. Therefore, bionic scaffolds with metal ion capture function are expected to become an important therapeutic strategy in bone tissue engineering.
[0159] In summary, the present invention prepares a PD-functionalized micro-nano 3D NS@PD scaffold that can capture Cu 2+ The mechanical properties are significantly improved, which solves the problem that the sponge scaffold has poor mechanical properties and cannot be used for bone repair. On the other hand, the 3D NS@PD scaffold of the present invention can capture Cu at multiple sites. 2+ To promote bone regeneration and release Cu stably for a long time2+ In vitro studies have shown that the 3D NS@PD scaffold can capture free Cu through multiple sites. 2+ At the same time, the captured Cu 2 + It can promote the osteogenic differentiation and angiogenesis of BMSCs. In vivo studies also showed that 3D NS@PD and 3D NS@PD@Cu(II) scaffolds accelerated the repair of bone damage by promoting angiogenesis, and 3D NS@PD@Cu(II) scaffolds had a strong local presence of Cu in the early stage of bone damage. 2+ , and has multiple sites to capture free Cu 2+ function.
Claims
1. A method for preparing a fiber sponge scaffold for promoting bone repair, improving mechanical properties and capturing copper ions at multiple sites, characterized in that: The method is to carry out π-π conjugation grafting of short nanofiber sponges and phosphorus-containing crown macromolecules containing multiple pyrrole groups to obtain a fiber sponge scaffold with multiple sites for capturing copper ions; The short nanofiber sponge is prepared by electrospinning collagen and polylactic acid to obtain a three-dimensional porous scaffold, which is then cross-linked with glutaraldehyde; the weight ratio of the collagen to the polylactic acid is 4:1; The method for preparing the phosphorus-containing crown macromolecule containing multiple pyrrole groups comprises the following steps: 1) Add potassium carbonate to the tetrahydrofuran solution of hexachlorocyclotriphosphazene, add stearic acid amide tetrahydrofuran solution dropwise at low temperature, react at room temperature, filter, and vacuum dry to obtain C 17 -Ph-(N3P3)-Cl5; 2) Add cesium carbonate to the tetrahydrofuran solution of p-hydroxybenzaldehyde, and then add the C obtained in step (1) dropwise. 17 -Ph-(N3P3)-Cl5 tetrahydrofuran solution, react at room temperature, filter, purify, and vacuum dry to obtain C 17 -Ph-(N3P3)-(Ph-CHO)5; 3) In C 17 -Ph-(N3P3)-(Ph-CHO)5 dichloromethane solution was added with anhydrous sodium sulfate, and thiophosphoryl chloride modified with methylenehydrazine was added dropwise under ice bath condition, stirred at room temperature overnight, filtered, purified, and dried in vacuo to obtain C 17 -Ph-(N3P3)-(Ph-P-Cl2)5; 4) In C 17 Potassium carbonate is added to the tetrahydrofuran solution of -Ph-(N3P3)-(Ph-P-Cl2)5, and the tetrahydrofuran solution of the pyrrole derivative HO-Ph-NC5 is added dropwise, stirred at room temperature overnight, rotary evaporated, purified, and vacuum dried to obtain the phosphorus-containing crown macromolecule containing multiple pyrrole groups.
2. The preparation method according to claim 1, characterized in that: The collagen is fish collagen.
3. The preparation method according to claim 1 or 2, characterized in that: The molecular weight of the polylactic acid is in the range of 30 to 50 kDa.
4. The preparation method according to claim 1 or 2, characterized in that: The collagen and polylactic acid are dissolved in hexafluoroisopropanol to prepare a spinning solution with a mass percentage of 10%, and then electrostatic spinning is performed.
5. The preparation method according to claim 1 or 2, characterized in that: The process parameters of the electrospinning are: voltage 18 kV, receiving distance 15 cm, and liquid feeding rate 3 mL / h.
6. The preparation method according to claim 1 or 2, characterized in that: The cross-linking time is 30 min.
7. A fiber sponge scaffold with improved mechanical properties and multi-site copper ion capture, prepared by the method according to any one of claims 1 to 6.
8. An application of the fiber sponge scaffold for improving mechanical properties and capturing copper ions at multiple sites as claimed in claim 7, characterized in that: The fiber sponge scaffold is used to prepare implant materials or drug carriers for promoting bone repair.